Contaminant Exposure and Liver and Kidney Lesions in North American River Otters in the Indian River Lagoon, Florida - Ami Krasner; Megan Stolen; David Rotstein; Spencer Fire (Toxics)
The harmful algal bloom (HAB) liver toxin microcystin (MC) and trace element biomagnification were previously detected in organisms in the Indian River Lagoon (IRL), Florida. Since there are no routine screening programs for these contaminants, liver tissue from North American river otters (Lontra canadensis), an important sentinel species in the IRL, was screened for MC via enzyme-linked immunoassay (ELISA), followed by confirmatory analyses via liquid-chromatography/mass spectrometry methods (LC-MS/MS). Liver and kidney samples were evaluated for trace element (As, Cd, Co, Cu, Fe, Hg, Mn, Mo, Pb, Se, Tl, and Zn) bioaccumulation via inductively coupled plasma mass spectrometry (ICP-MS). Histopathologic evaluation of the liver and kidney was conducted to assess possible correlation with toxic insults. Forty-three river otters were evaluated (2016–2022). Microcystin was not detected in any river otter sample (n = 37). Of those tested for trace element bioaccumulation (n = 22), no sample measured above provided reference ranges or estimated toxic thresholds for this species. There were no statistically significant patterns observed based on season, year, or age class, but sex had a small influence on trace element levels in the kidney. One individual had a kidney Cu level (52 μg/g dry weight) higher than any previously reported for this species. Trace elements were detected at presumed background levels providing baselines for future monitoring. For otters with available histopathologic evaluation (n = 28), anomalies indicative of contaminant exposure (non-specific inflammation, necrosis, and/or lipidosis) were present in the liver and kidney of 18% and 4% of individuals, respectively. However, since these lesions were not linked to abnormal trace element bioaccumulation or MC exposure, other causes (e.g., infectious disease) should be considered.